Pena.lt/y - Eastwood, M. (2017)
Pena.lt/y is the home of Martin Eastwood's research into football analytics. Areas of interest for the pena.lt/y site include the application of statistics and data science to transfers and player analytics, predictive modeling of goals, fixture results and much more.